Impact of blindness due to cataract in elderly fallers: findings from a cross-sectional study in Andhra Pradesh, South India - Krishnaiah, Sannapaneni (BMC Res Notes, 2018)
OBJECTIVE: To estimate the prevalence of falls, frequency of falls, injury due to falls and to explore the relationship between cataract-related blindness and falls in older patients above or equal to 50 years of age. RESULTS: A cross-sectional study was conducted to investigate the relationship between cataract related blindness and risk of fall. Details about any fall in the previous 12 months and systemic illness history were collected through a personal interview. Overall, 70 (18.3%; 95% confidence intervals (CI) 14.4%, 22.2%) of the 382 patients investigated had experienced falls. The history of recurrent falls were more commonly seen in patients with bilateral cataract (p = 0.023). The mean presenting Logarithm of the Minimum Angle of Resolution (LogMAR) visual acuity was significantly higher in fallers when compared to non-fallers: 0.81 ± 0.41 versus 0.65 ± 0.31 (p = 0.001). The prevalence of falls was significantly higher in patients with bilateral cataract blind; adjusted odds ratio (OR): 1.76 (p = 0.042). Timely diagnosis and surgical intervention in patients with bilateral blindness due to cataract may help prevent falls in older patients in Andhra Pradesh, South India.